2020
DOI: 10.1016/j.combustflame.2019.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Near-lean blowoff dynamics in a liquid fueled combustor

Abstract: This paper describes an analysis of the near-lean blow off(LBO) dynamics of spray flames, including the influence of fuel composition upon these dynamics. It is motivated by the fact that, while reasonable correlations exist for predicting blowoffconditions, the fundamental reasons for why flames supported by flow recirculation actually blow offare not well understood. Prior work on gaseous systems has shown that the blowoffevent is a culmination of several intermediate processes, initiating with local extinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…Additionally, for the two kerosene flames, it was observed that the one with a higher DCN (A2 in this case) was more stable, which is consistent with the findings in Ref. [17].…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Additionally, for the two kerosene flames, it was observed that the one with a higher DCN (A2 in this case) was more stable, which is consistent with the findings in Ref. [17].…”
Section: Resultssupporting
confidence: 92%
“…Such localized increase in OH* signal may be associated with the continuous re-ignition of the flame in RZ as observed by Ref. [17].…”
Section: B Flame Shapesupporting
confidence: 53%
See 3 more Smart Citations